2014
DOI: 10.1016/j.asieco.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Interest rate pass-through and monetary policy asymmetry: A journey into the Caucasian black box

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Similarly, Neumark and Sharpe (1992) showed that partial reason for asymmetry in bank deposit market is high level of concentration. These findings mean that commercial banks with monopoly power increase deposit rates slowly, but decrease the rates quickly (Jamilov and Egert, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 89%
See 2 more Smart Citations
“…Similarly, Neumark and Sharpe (1992) showed that partial reason for asymmetry in bank deposit market is high level of concentration. These findings mean that commercial banks with monopoly power increase deposit rates slowly, but decrease the rates quickly (Jamilov and Egert, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 89%
“…Consumer reaction hypothesis argue that, when retail banks operate in a competitive market condition, they would refrain from the negative reactions of consumers due to lending rate increases or deposit rate decreases. In case of asymmetric adjustment conditions, lending rates would be rigid upwards and deposit rates would be rigid downwards (Jamilov and Egert 2014). However, bank's collusive price hypothesis argue that retail banks are more likely to decrease deposit rates and increase lending rates, in case of banks able to abuse monopoly power and arrange IRs based on their interests (Kargianniset.al., 2010, pp.3-5).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Jamilov & Égert analyze and evaluate the interest rate pass-through as an empirical evaluation for the Caucasus region: Armenia, Azerbaijan, Georgia, Kazakhstan, and Russia [9]. They use the autoregressive distributed lag (ARDL) method.…”
Section: Theory and Literatur Reviewmentioning
confidence: 99%